Superoxide Anion and Hydroxyl Radical Release by Collagen-induced Platelet Aggregation - Role of Arachidonic Acid Metabolism - Caccese, Daniela; Praticò, Domenico; Ghiselli, Andrea; Natoli, Silvia; Pignatelli, Pasquale; Sanguigni, Valerio; Iuliano, Luigi; Violi, Francesco (Thrombosis and Haemostasis, 2000)
Previous study demonstrated that platelets undergoing anoxia-reoxygenation generate superoxide anion (O2−) and hydroxyl radical (OH°) which in turn contribute to activate arachidonic acid (AA) metabolism. However it has not been clarified if oxygen free radicals (OFRs) are also generated when platelets are aggregated by common agonists. We used two probes, i.e. lucigenin and salicylic acid (SA), to measure platelet release of O2− and OH°, respectively. Among the agonists used, such as ADP, thrombin and collagen, the release of O2− and OH° was observed mainly when platelets were stimulated with collagen. Such release was inhibited in platelets pre-treated by aspirin suggesting that AA metabolism was the main source of O2− and OH° formation. To further analyze this relationship, O2 and OH° formation was measured if other oxidant species, namely O2− and OH°, contribute to the during AA-stimulated platelet aggregation (PA); we observed that O − and OH° release were dependent upon AA concentration. Furthermore, we found that the incubation of platelets with AACOCF3, a potent inhibitor of cytosolic phospholipase A2, inhibited collagen-induced platelet O− and OH° release. The incubation of platelets with salicylic acid or ascorbic acid, which blunt OH° and O2− respectively, inhibited both collagen-induced platelet aggregation and AA-release. This study demonstrated that collagen-induced platelet aggregation is associated with O2− and OH° formation, which is dependent upon AA release and analyzed if O2− and OH° are released during aggregation induced by metabolism.
Keywords: Platelet aggregation; free radicals; superoxide anion; arachidonic acid metabolism; collagen